Soccer-related performance in eumenorrheic Tunisian high-level soccer players: effects of menstrual cycle phase and moment of day - Tounsi, M.; Jaafar, H.; Aloui, A.; Souissi, N. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study aimed to examine the combined effects of menstrual cycle phase and moment of day on female soccer players' performances in the five-jump test (5JT), the repeated shuttle-sprint ability test (RSSA), and the Yo-Yo intermittent recovery test level 1 (YYIRT1).